Endovascular repair versus surgery for mycotic aneurysm a retrospective study with Bayesian inference - Taiji Koyama; Kentaro Iwata; Katsuhiro Yamanaka; Kenji Okada; Chisato Miyakoshi (Surgery in Practice and Science, 2022)
Introduction: Because mycotic aneurysm is a rare infection, the effectiveness of endovascular aneurysm repair (EVAR) and thoracic endovascular aortic repair (TEVAR) for mycotic aneurysm is difficult to evaluate. Methods: We conducted a retrospective cohort study comparing EVAR/TEVAR and surgical repair (SR), using both Cox proportional regression analysis and Bayesian inference for patients with mycotic aneurysm diagnosed between January 2008 and December 2015. Results: A total of 38 patients with mycotic aneurysm were included in the study. Eight patients (21%) received EVAR/TEVAR and the remaining 30 (79%) underwent surgery (SR). The median duration of survival (or follow up) for the EVAR/TEVAR group was 916 days (range 66–2053 days), whereas the median duration for the SR group was 1550 days (range 1–4825 days). The hazard ratio using the Cox proportional hazards model showed a hazard ratio (HR) of 2.25 (95% confidence interval 0.82–6.17, p = 0.11).The posterior probability density of each treatment group was derived by the Markov chain Monte Carlo (MCMC) method and the calculated HR was 1.68, with 95% credible interval 0.68–4.35. Discussion: Although the post-operative life expectancy tended to be longer following SR, EVAR/TEVAR could be an option when SR is not feasible.